2008
DOI: 10.1108/13565360810889629
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductive cells from screen‐printed and sintered cadmium sulfoselenide

Abstract: PurposeScreen‐printing is an appropriate technique for the manufacture of large‐area position‐sensitive detectors. The purpose of this paper is to present simple methods of paste preparation and appropriate processing of thick films.Design/methodology/approachActive layers of photoconductive cells based on doped CdS0.32Se0.68 were prepared by screen‐printing and sintering at 530°C. A sulfide‐selenide mixture or a mixed crystal material and propylene glycol (PG) was deposited as a paste. PG served as the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Most conventional LDRs based on inorganic materials require high temperature processes for sintering and crystallization steps. In this regard, a couple of studies have been reported for solution-processed inorganic LDRs even though a temperature higher than 300 °C was still required to control grain sizes and crystallization processes for bismuth sulfide (Bi 2 S 3 ) etc . In addition, most inorganic materials used for conventional LDRs contain toxic and environmentally hazardous elements, such as cadmium (Cd) and lead (Pb), so that their applications have been gradually restricted by various environmental regulations …”
Section: Introductionmentioning
confidence: 99%
“…Most conventional LDRs based on inorganic materials require high temperature processes for sintering and crystallization steps. In this regard, a couple of studies have been reported for solution-processed inorganic LDRs even though a temperature higher than 300 °C was still required to control grain sizes and crystallization processes for bismuth sulfide (Bi 2 S 3 ) etc . In addition, most inorganic materials used for conventional LDRs contain toxic and environmentally hazardous elements, such as cadmium (Cd) and lead (Pb), so that their applications have been gradually restricted by various environmental regulations …”
Section: Introductionmentioning
confidence: 99%
“…Films made of CdS and CdSe are known for their high photoconductivity and photosensitivity. Photoresistors based on these materials are widely used in applications such as photodetectors and optical couplers [2][3][4][5]. The investigations of photoconductive CdSe and CdS systems have a long history, see e.g.…”
Section: Introductionmentioning
confidence: 99%